Study of Some Power Influencing Parameters of a Solar Low Temperature Stirling Engine - Hassani, Hind El; Boutammachte, N.; Hannaoui, M. (European Journal of Sustainable Development, 2014)
The aim of this paper is to study experimentally and theoretically the effect of some geometrical parameters on low temperature differential Stirling engines (LT-SE) performance. The studied parameters are: the phase angle, the compression ratio and the dead volume. Results show that for optimizing the performance of these engines, dead volume should be minimized, the compression ratio should be maximized and the optimal phase angle for the gamma type is 90°. For the adopted theoretical model, based on Schmidt theory, even if theoretical numerical results are different from those found experimentally, but it still remains a valid model for finding out some parameters effect on the LT-SE performance, and for calculating approximately the engine work and power. Key words: Stirling engine, low temperature, Solar, Phase angle, compression ratio, dead volume.